PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTUAN MEDIA CARD SITUATION TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS IV SD NEGERI LAMSAYEUN ACEH BESAR - Syifa Neujidia; Mislinawati; Nurmasyitah (STKIP Subang, 2026)
This study aimed to determine the effect of the Discovery Learning model assisted by Card Situation media on the learning outcomes of fourth-grade students in Pancasila Education, specifically on the topic of rights and obligations, at SD Negeri Lamsayeun, Aceh Besar Regency. This study was motivated by the low learning outcomes of students on this topic, as indicated by a number of students who had not yet met the Minimum Learning Achievement Criteria (KKTP) of 75. The research used a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The research population consisted of 42 fourth-grade students, divided into an experimental class and a control class with 21 students each. Data were collected through pretest and posttest instruments in the form of 20 multiple-choice items. The data were analyzed using the N-Gain test, normality test, homogeneity test, and independent sample t-test. The results showed that the average N-Gain score of the experimental class was 0.76 (high category), while the control class obtained an average N-Gain score of 0.35 (moderate category). The hypothesis testing showed a significance value (Sig. 2-tailed) of 0.000 < 0.05,), indicating that the Discovery Learning model assisted by Card Situation media had a significant effect on students' learning outcomes in Pancasila Education on the topic of rights and responsibilities. It can therefore be concluded that the Discovery Learning model assisted by Card Situation media has a significant effect on the learning outcomes of fourth-grade students in Pancasila Education on the topic of rights and obligations at SD Negeri Lamsayeun, Aceh Besar.